Hydrodynamic performance and wake study of an UUV sailing near the free surface - Zhang, Dapeng; Zhao, Bowen; Sun, Jiyuan (Frontiers in Marine Science, 2024)
In this study, the SUBOFF UUV is numerically modelled in order to investigate the hydrodynamic features and effects of submerged navigation near the free surface. At various speeds and depths below the surface, the hydrodynamic behaviors of the SUBOFF UUV are examined. From the CFD results, we can deduce that submergence depth significantly affects total resistance of SUBOFF navigation nearby free surface. Because the Kelvin wake of SUBOFF creates wave-making resistance when approaching the open surface head-on, the fraction of pressure difference resistance becomes dramatically with an increase in Fr. The principle of superposition of the divergent wave system and the transverse wave system gradually reveals the divergent wave system as Fr grows larger. The wave making energy is greater, and the UUV needs more power to overcome the wave making resistance.